Navigating Employee Performance: The Synergy of Ethical Leadership, Communication Proficiency and Trust - Hasnidar, Hasnidar; Jusri, Jusri; Bakri, Asri Ady (Escalate : Economics and Business Journal, 2023)
This study aims to investigate the factors influencing Employee Performance within the South Sulawesi Provincial Secretariat, with a focus on Ethical Leadership, Communication, and Trust. The primary objective is to understand the individual and combined impacts of these factors on performance outcomes. A quantitative approach was employed, involving a sample of 56 employees from the South Sulawesi Provincial Secretariat. Data was collected through structured surveys, and statistical analysis, including regression analysis using SPSS, was conducted to examine the relationships between Ethical Leadership, Communication, Trust, and Employee Performance. The findings revealed compelling insights into the factors affecting Employee Performance. Ethical Leadership was identified as a significant positive influencer, emphasizing the importance of leaders upholding ethical principles. Effective Communication emerged as a crucial factor, highlighting the need for clear and transparent communication channels to improve performance. Trust also played a vital role, underlining the significance of trust-building initiatives within the organization. Additionally, when these factors were considered together, they collectively and significantly impacted Employee Performance, highlighting the value of an integrated approach.